The vernalisation regulator FLOWERING LOCUS C is differentially expressed in biennial and annual Brassica napus - Schiessl, Sarah V. (Sci Rep, 2019)
Plants in temperate areas evolved vernalisation requirement to avoid pre-winter flowering. In Brassicaceae, a period of extended cold reduces the expression of the flowering inhibitor FLOWERING LOCUS C (FLC) and paves the way for the expression of downstream flowering regulators. As with all polyploid species of the Brassicaceae, the model allotetraploid Brassica napus (rapeseed, canola) is highly duplicated and carries 9 annotated copies of Bna.FLC. To investigate whether these multiple homeologs and paralogs have retained their original function in vernalisation or undergone subfunctionalisation, we compared the expression patterns of all 9 copies between vernalisation-dependent (biennial, winter type) and vernalisation-independent (annual, spring type) accessions, using RT-qPCR with copy-specific primers and RNAseq data from a diversity set. Our results show that only 3 copies – Bna.FLC.A03b, Bna.FLC.A10 and to some extent Bna.FLC.C02 – are differentially expressed between the two growth types, showing that expression of the other 6 copies does not correlate with growth type. One of those 6 copies, Bna.FLC.C03b, was not expressed at all, indicating a pseudogene, while three further copies, Bna.FLC.C03a and Bna.FLC.C09ab, did not respond to cold treatment. Sequence variation at the COOLAIR binding site of Bna.FLC.A10 was found to explain most of the variation in gene expression. However, we also found that Bna.FLC.A10 expression is not fully predictive of growth type.